Development of a positioning aid to reduce postural variability and errors in 3D whole body scan measurements. (April 2018) - Schwarz-Müller, Frank; Marshall, Russell; Summerskill, Steve
Abstract: Three-dimensional (3D) body scanners have the potential to evaluate changes to the human form through different clothing configurations, the use of protective equipment, or the effects of medical interventions. To achieve this, scans of an individual need to be superimposed for each experimental condition. The literature highlights that one of the limiting factors is postural variability. This paper describes a newly developed 'positioning aid' that stabilises the posture during the scanning process and is invisible on scans. The results of a study evaluating the efficacy of the positioning aid showed that it reduces postural variability for all body parts in lateral and longitudinal directions. A reference test with a rigid mannequin indicated that the 'technical' variability due to the scanner hardware and software significantly contributes to the residual variability. Furthermore, the study showed that the newly developed positioning aid overall increased the precision of the software-assisted extraction of body dimensions. Highlights: A positioning aid predominantly made of Plexiglas was developed for body scanners. Being invisible on scans it did not adversely affect measurement extraction. A study assessed the efficacy of the positioning aid in reducing human variability. Human variability was reduced for all body parts both laterally and longitudinally. An extra fixture for the shoulders is required to further reduce human variability.